Research on Intelligent Security Access Platform Based on SDN - Peng LI; Yueping YANG; Yang YANG (天地一体化信息网络)
Firstly, the difficulty of upgrading and expanding the traditional security service equipment were analyzed, and a design of an intelligent security access platform was proposed.Then, the research and development ideas and technical routes of the intelligent security access platform were explained, and hardware and software were designed.Finally, the platform achievement test and application deployment construction were carried out to verify the value of the platform.